A comparative study of the internationalization of higher education policy in Australia and China (2008–2015). Issue 4 (2nd April 2020) - Hong, Min
ABSTRACT: In an era of globalization, internationalization of higher education (IHE) has been constructed as an almost inevitable trend and has become a common pursuit of many nations in their higher education (HE) policies. This study focuses on two nations, China and Australia, in terms of this trend. The broadest aim of this research was to find out the interactive relationships between global and national pressures in policy development by comparing the international HE policies in China and Australia, for the period 2008–2015. Based on selected policies, Similarities and differences in the three categories, overarching meta-policies at the macro level (nation), institution focused polices at the meso level (universities), and people focused policies at the micro level (individuals) are identified in this study. It is suggested that different responses to the global trends reflect the specificities of each nation and the ways path dependent factors mediate global pressures. This comparison will facilitate better understanding of how globalization has affected and been responded to in IHE policies, and enable better understanding of their path dependent mediation through a focus on two specific sets of national policies.